N-(2-Methylphenylsulfonyl)acetamide - Shakuntala, K. (International Union of Crystallography, 2011)
In the molecular structure of the title compound, C(9)H(11)NO(3)S, the N—H and C=O bonds are anti to each other, while the amide H atom is syn with respect to the ortho-methyl group in the benzene ring. The C—S—N—C torsion angle is −58.2 (2)°, indicating a twist in the molecule. In the crystal, N—H⋯O hydrogen bonds link the molecules into chains along the c axis.